Thyroid response to blocking sympathetic activity in chronic cold-exposed hunters in East Greenland: a case–control study - Mette Motzfeldt Jensen; Charlotte Elberling Almasi; Hans Christian Florian-Sørensen; Stine Linding Andersen; Stig Andersen (European Thyroid Journal)
Background: Thyroid hormones and sympathetic stimulation are needed for activating brown adipose tissue (BAT) during cold exposure. Studies of human cold exposure have demonstrated both increased production and raised clearance of triiodothyronine (T3). Greenlandic hunters provide a unique model for evaluating metabolic effects of cold exposure. Aim: We aimed to explore the dynamics of thyroid hormones when blocking sympathetic activity in Greenlandic hunters during winter to inspire knowledge on mechanisms of BAT activation. Methods: We conducted a 7-day field study of Greenlandic hunters (n = 7) in East Greenland in February. The sympathetic system was blocked using a non-selective beta blocker for seven consecutive days. A group of non-hunter Greenlanders (n = 8) from the same settlement was included for parallel sampling. All participants were healthy men. Blood samples were drawn daily for measurement of TSH, thyroid hormone levels and thyroglobulin. Results: Hunters had higher serum thyroglobulin, TSH and fT3/fT4 ratio compared to controls. Blocking the sympathetic activity was followed by changes in serum thyroglobulin and fT3 with an initial decrease and subsequent restoration of levels, while TSH and fT4 showed a gradual increase over the course of the study. The fT3/fT4 ratio showed a continuous and marked decrease. Conclusion: We speculate that when blocking the sympathetic system, TSH increases to uphold the production of T3 needed for maintaining BAT activity. In addition, alterations of fT3/fT4 ratio support a hypothesis of adrenergic stimulation promoting T3 over T4 secretion from the thyroid via adrenergic nerve terminals in the thyroid.